Transfer device and image forming device

By using the second annular belt and the first annular belt of a specific structure in the image forming device, the resistance rise and discharge mark hole problems of the secondary transfer member are solved, and the image quality is improved.

CN113031418BActive Publication Date: 2025-04-15FUJIFILM BUSINESS INNOVATION CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202010512174.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-06
Filing Date
2020-06-08
Publication Date
2025-04-15
Estimated Expiration
2040-06-08

AI Technical Summary

Technical Problem

In an image forming device using electrophotography, the increase in the resistance of the secondary transfer member and the problem of discharge mark holes when thick paper is continuously removed, resulting in a decrease in image quality.

Method used

A transfer device is designed which uses a second annular belt and a first annular belt having a specific conductive layer structure. The conductive layer of the second annular belt includes an ionic conductive organic polymer material and an agglomerate of an electron conductive conductive conferencing agent. The particle size is 100 nm or more than 3 μm, the number of islands is 20 or more than 50 in a 10 μm x 10 μm square, and the commonly used logarithmic value of volume resistivity is 10.0LogΩ·cm or more than 12.5LogΩ·cm or less. The spatial distribution characteristics of conductive carbon particles in the first annular belt are suppressed by adjusting the integral value of the statistic L(r) of the interparticle distance to 0 or less, and the generation of discharge trace holes is suppressed.

Benefits of technology

The generation of discharge mark holes in the second annular belt is effectively suppressed, and the high quality of the image is maintained, especially when thick paper is continuously removed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113031418B_ABST
    Figure CN113031418B_ABST
Patent Text Reader

Abstract

The present application relates to a transfer device and an image forming device. The transfer device comprises: an intermediate transfer body as a first endless belt, the first endless belt is a first endless belt containing resin and conductive carbon particles, the conductive carbon particles existing in the evaluation area of ​​6.3μm×4.2μm on the outer peripheral surface satisfy a specific spatial distribution; a primary transfer mechanism, which transfers a toner image formed on the surface of an image holding body to the surface of the intermediate transfer body; and a secondary transfer mechanism, which has a second endless belt arranged on the outer peripheral surface side of the intermediate transfer body, and is a secondary transfer mechanism for secondary transferring the toner image transferred to the surface of the intermediate transfer body to the surface of a recording medium on the second endless belt, and the second endless belt has a specific conductive layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a transfer device and an image forming device. Background Art

[0002] In an image forming device (copier, fax machine, printer, etc.) using an electrophotographic method, a toner image formed on the surface of an image holder is transferred to the surface of a recording medium and fixed on the recording medium to form an image. It should be noted that in the transfer of such a toner image to the recording medium, a conductive endless belt such as an intermediate transfer belt is used.

[0003] For example, Japanese Patent Publication No. 2017-181604 discloses "a conductive component for an image forming device, comprising a conductive layer, the conductive layer having a sea portion comprising a conductive organic polymer material and an island portion consisting of an agglomerate of an electron-conductive conductivity-imparting agent and having a particle size of 100 nm to 3 μm, wherein the number of the island portions in a 10 μm×10 μm square is 20 to 50."

[0004] Japanese Patent Application Laid-Open No. 2007-011117 discloses “an intermediate transfer belt having at least a surface layer on a substrate, wherein the surface layer contains aggregates of conductive particles having an average particle size of 0.5 to 25 μm”. Summary of the invention

[0005] Technical problem to be solved by the invention

[0006] In a transfer device in which the toner transferred to the surface of the first endless belt (intermediate transfer body) is transferred to a recording medium by a secondary transfer mechanism having a second endless belt (secondary transfer member), when an endless belt having a conductive layer containing an ion-conductive organic polymer material and an electron-conductive conductivity-imparting agent is used as the second endless belt, resistance may increase due to repeated application of high voltage as the second endless belt is used continuously. As a method for suppressing the resistance increase, for example, a method can be cited in which the number of island portions composed of aggregates of the electron-conductive conductivity-imparting agent and having a particle size of 100 nm or more and 3 μm or less is 20 or more and 50 or less in a 10 μm×10 μm square, and the common logarithm value of the volume resistivity of the second endless belt as a whole is 10.0 LogΩ·cm or more and 12.5 LogΩ·cm or less.

[0007] However, the second annular zone having the common logarithmic values ​​of the number of islands and the volume resistivity within the above ranges can suppress the increase in resistance, but when the basis weight is greater than 300 g / m 2 When thick paper is continuously fed, abnormal discharge at the end of the paper may cause discharge marks on the surface of the endless belt as the secondary transfer member.

[0008] The technical problem to be solved by the present invention is to provide a transfer device, which can suppress the generation of discharge trace holes in the second annular band compared with the case where the number of the above-mentioned island portions in the second annular band is greater than 20 and less than 50, the common logarithm of the volume resistivity of the second annular band as a whole is greater than 10.0 LogΩ·cm and less than 12.5 LogΩ·cm, and the integral value of the statistic L(r) in the first annular band is greater than 0.1.

[0009] Means for solving technical problems

[0010] According to a first aspect of the present invention, there is provided a transfer device comprising:

[0011] The intermediate transfer body as the first endless belt is a first endless belt comprising a resin and conductive carbon particles, wherein in the spatial distribution of the conductive carbon particles existing in the evaluation area of ​​6.3 μm×4.2 μm on the outer peripheral surface, the integral value of the statistic L(r) represented by the following formula (1) in which the inter-particle distance r is 0.05 μm or more and 0.30 μm or less is 0 or more and 0.1 or less;

[0012] a primary transfer mechanism for primarily transferring the toner image formed on the surface of the image holding body to the surface of the intermediate transfer body; and

[0013] A secondary transfer mechanism, which has a second annular belt arranged on the outer peripheral surface side of the above-mentioned intermediate transfer body, is a secondary transfer mechanism for secondary transferring the above-mentioned colorant image transferred to the surface of the above-mentioned intermediate transfer body to the surface of the recording medium on the above-mentioned second annular belt, the above-mentioned second annular belt has a conductive layer, the conductive layer has a sea portion containing an ion conductive organic polymer material and an island portion composed of an agglomerate of an electronic conductive conductivity imparting agent and with a particle size of not less than 100nm and not more than 3μm, the number of the above-mentioned island portions in a 10μm×10μm square of the above-mentioned conductive layer is not less than 20 and not more than 50, and the common logarithm value of the volume resistivity of the above-mentioned second annular belt as a whole is not less than 10.0LogΩ·cm and not more than 12.5LogΩ·cm.

[0014] [Number 1]

[0015]

[0016] In the above formula (1), r represents the above inter-particle distance, and K(r) represents Ripley's K function K(r) represented by the following formula (2).

[0017] [Number 2]

[0018]

[0019] In the above formula (2), 1(|X i -X j |≦r) represents the indicator function, X i and X j Represent the coordinates of point i and point j respectively, |X i -X j | represents coordinate X i With coordinate X j The Euclidean distance, r represents the distance between the above particles, s(|X i -X j |) represents the edge correction coefficient s(x) of the evaluation area represented by the following formula (3), x=|X i -X j |, N represents the total number of particles in the evaluation area, and λ represents the number density of particles in the evaluation area.

[0020] [Number 3]

[0021]

[0022] In the above formula (3), L x and L y represents the length of the side in the x-axis direction and the y-axis direction of the evaluation area (μm), x=|X i -X j |, X i and X j Represent the coordinates of point i and point j respectively, |X i -X j | represents coordinate X i With coordinate X j The Euclidean distance of .

[0023] According to the second aspect of the present invention, the common logarithm value of the volume resistivity of the second annular zone as a whole is not less than 10.0 LogΩ·cm and not more than 11.6 LogΩ·cm.

[0024] According to a third aspect of the present invention, the organic polymer material is a rubber material.

[0025] According to a fourth aspect of the present invention, the rubber material includes at least one selected from the group consisting of epichlorohydrin rubber, chloroprene rubber, and acrylonitrile-butadiene copolymer rubber.

[0026] According to a fifth aspect of the present invention, the rubber material includes epichlorohydrin rubber, chloroprene rubber, acrylonitrile-butadiene copolymer rubber, and ethylene-propylene-diene terpolymer rubber.

[0027] According to a sixth aspect of the present invention, the conductivity-imparting agent is carbon black.

[0028] According to a seventh aspect of the present invention, the resin includes at least one selected from the group consisting of polyimide resins, polyamide-imide resins, aromatic polyetheretherketone resins, polyphenylene sulfide resins, and polyetherimide resins.

[0029] According to an eighth aspect of the present invention, the resin includes a polyimide resin.

[0030] According to a ninth aspect of the present invention, the number average primary particle size of the conductive carbon particles is not less than 10 nm and not more than 20 nm.

[0031] According to a tenth aspect of the present invention, the number average primary particle size of the conductive carbon particles is not less than 10 nm and not more than 15 nm.

[0032] According to an eleventh aspect of the present invention, the conductive carbon particles are channel black.

[0033] According to a twelfth aspect of the present invention, the number average primary particle size of the conductive carbon particles is not less than 0.1 times and not more than 1.0 times the number average primary particle size of the electronically conductive conductivity-imparting agent.

[0034] According to a thirteenth aspect of the present invention, there is provided an image forming apparatus comprising:

[0035] Image holding body,

[0036] A charging device is used to charge the surface of the image holding body.

[0037] An electrostatic latent image forming device forms an electrostatic latent image on the charged surface of the image holding body.

[0038] a developing device storing a developer including a toner, and developing the electrostatic latent image formed on the surface of the image holding member using the developer to form a toner image, and

[0039] The transfer device transfers the toner image to the surface of the recording medium.

[0040] Effects of the Invention

[0041] According to the above-mentioned schemes 1, 2, 3, 4, 5, 6, 7, or 8, a transfer device is provided. Compared with the case where the number of the above-mentioned island portions in the second annular band is greater than 20 and less than 50, the common logarithm value of the volume resistivity of the second annular band as a whole is greater than 10.0 LogΩ·cm and less than 12.5 LogΩ·cm, and the integral value of the statistic L(r) in the first annular band is greater than 0.1, the transfer device of the above scheme can suppress the generation of discharge trace holes in the second annular band.

[0042] According to the ninth aspect, there is provided a transfer device which can suppress the generation of discharge trace holes in the second endless belt, compared with a case where the number average primary particle size of the conductive carbon particles is larger than 20 nm.

[0043] According to the tenth aspect, there is provided a transfer device which can suppress the generation of discharge trace holes in the second endless belt, compared with a case where the number average primary particle size of the conductive carbon particles is larger than 15 nm.

[0044] According to the eleventh aspect, there is provided a transfer device which can suppress the generation of discharge trace holes in the second endless belt, compared with the case where the conductive carbon particles are furnace black.

[0045] According to the above-mentioned scheme 12, a transfer device is provided, which can suppress the generation of discharge trace holes in the second annular belt compared to the case where the number average primary particle size of the conductive carbon particles is larger than 1.0 times the number average primary particle size of the electronically conductive conductivity-imparting agent.

[0046] According to the above-mentioned scheme 13, an image forming device is provided. Compared with a transfer device in which the number of the above-mentioned island portions in the second annular belt is greater than 20 and less than 50, the common logarithm value of the volume resistivity of the second annular belt as a whole is greater than 10.0 LogΩ·cm and less than 12.5 LogΩ·cm, and the integral value of the statistic L(r) in the first annular belt is greater than 0.1, the image forming device of this scheme can form an image with suppressed whitening caused by the discharge trace holes in the second annular belt. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 (A) is a schematic plan view showing an example of a circular electrode.

[0048] Figure 1 (B) is a schematic cross-sectional view showing an example of a circular electrode.

[0049] Figure 2 This is a schematic structural diagram showing an example of the image forming apparatus according to the present embodiment. DETAILED DESCRIPTION

[0050] The present embodiment will be described below. These descriptions and examples are provided to illustrate the embodiment and are not intended to limit the scope of the embodiment.

[0051] In the numerical range recorded in stages in the present embodiment, the upper limit or lower limit recorded in a numerical range can be replaced by the upper limit or lower limit of the numerical range in other stages recorded. In addition, in the numerical range recorded in the present embodiment, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment.

[0052] The term "step" in the present embodiment includes not only an independent step but also a step that cannot be clearly distinguished from other steps as long as the intended purpose of the step can be achieved.

[0053] While the embodiments of the present embodiment are described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the sizes of the components in the drawings are schematic, and the relative relationship between the sizes of the components is not limited to this.

[0054] Each component in the present embodiment may include two or more corresponding substances. When referring to the amount of each component in the composition in the present embodiment, when there are two or more substances corresponding to each component in the composition, unless otherwise stated, it refers to the total amount of the two or more substances present in the composition.

[0055] [Transfer device]

[0056] The transfer device of this embodiment comprises a first endless belt, which is an intermediate transfer body, a primary transfer mechanism and a secondary transfer mechanism, wherein the first endless belt is a first endless belt comprising resin and conductive carbon particles, and in the spatial distribution of the conductive carbon particles existing in the evaluation area of ​​6.3 μm×4.2 μm on the outer peripheral surface, the integral value of the statistic L(r) represented by the following formula (1) in which the distance r between particles is greater than or equal to 0.05 μm and less than or equal to 0.30 μm is greater than or equal to 0.1; the primary transfer mechanism transfers the toner image formed on the surface of the image holding body to the surface of the intermediate transfer body for the first time; the secondary transfer mechanism has a peripheral portion provided on the outer peripheral portion of the intermediate transfer body. The second annular belt on the surface side is a secondary transfer mechanism for secondary transferring the toner image transferred to the surface of the intermediate transfer body to the surface of the recording medium on the second annular belt. The second annular belt has a conductive layer, and the conductive layer has a sea portion and an island portion. The sea portion contains an ion conductive organic polymer material, and the island portion is composed of an agglomerate of an electronically conductive conductivity imparting agent and has a particle size of not less than 100nm and not more than 3μm. The number of the above-mentioned island portions in a 10μm×10μm square of the conductive layer is not less than 20 and not more than 50. The common logarithm value of the volume resistivity of the second annular belt as a whole is not less than 10.0LogΩ·cm and not more than 12.5LogΩ·cm.

[0057] [Number 4]

[0058]

[0059] In the above formula (1), r represents the above inter-particle distance, and K(r) represents Ripley's K function K(r) represented by the following formula (2).

[0060] [Number 5]

[0061]

[0062] In the above formula (2), 1(|X i -X j |≦r) represents the indicator function, X i and X j Represent the coordinates of point i and point j respectively, |X i -X j | represents coordinate X i With coordinate X j The Euclidean distance, r represents the distance between the above particles, s(|X i -X j |) represents the edge correction coefficient s(x) of the evaluation area represented by the following formula (3), x=|X i -X j |, N represents the total number of particles in the evaluation area, and λ represents the number density of particles in the evaluation area.

[0063] [Number 6]

[0064]

[0065] In the above formula (3), L x and L y represents the length of the side in the x-axis direction and the y-axis direction of the evaluation area (μm), x=|X i -X j |, X i and X j Represent the coordinates of point i and point j respectively, |X i -X j | represents coordinate X i With coordinate X j The Euclidean distance of .

[0066] Hereinafter, in the spatial distribution of conductive carbon particles existing in the evaluation area of ​​6.3μm×4.2μm on the outer peripheral surface of the first annular belt, the integral value of the statistic L(r) represented by formula (1) in which the inter-particle distance r is greater than 0.05μm and less than 0.30μm is also referred to as the "L(r) integral value".

[0067] In addition, the sea portion comprising an ion-conductive organic polymer material and the island portion composed of an agglomerate of an electronically conductive conductivity-imparting agent and having a particle size of greater than 100 nm and less than 3 μm (referred to as a “specific island portion”), and the number of specific island portions in a 10 μm×10 μm square of the conductive layer is referred to as the “island portion number”.

[0068] Here, the spatial distribution of the conductive carbon particles is obtained as follows: the outer peripheral surface of the first endless belt is observed by a scanning electron microscope (e.g., manufactured by Hitachi High-Technologies, model: SU8010) at a magnification of 20,000 times, and the obtained 256-level grayscale image is binarized as needed using analysis software (e.g., free software "ImageJ") with a threshold of 128, thereby obtaining the spatial distribution. Thereafter, based on the above formula, the statistic L (r) value for the inter-particle distance r of 0.05 μm or more and 0.30 μm or less is calculated for each 0.05 μm, and the integral value of the range of 0.05 μm or more and 0.30 μm or less is obtained.

[0069] The particle size of the island portion formed of the agglomerates of the conductivity imparting agent refers to the maximum diameter of the island portion. The diameter and the number of the island portions are measured by observing the cross section of the second annular zone. The specific method is as follows.

[0070] The second annular band was cut along the thickness direction with a single-edged razor, and the cross section was observed with a scanning electron microscope (SEM). The portion with low contrast during cross-sectional observation was regarded as an island, and the maximum diameter of each island in one field of view was measured.

[0071] Thereafter, the number of island portions in a 10 μm×10 μm square was calculated from the measurement results of the diameters of the island portions.

[0072] In this embodiment, compared with the case where the number of the islands in the second annular zone is 20 to 50, the common logarithm value of the volume resistivity of the second annular zone as a whole is 10.0 LogΩ·cm to 12.5 LogΩ·cm, and the integral value of the statistic L(r) in the first annular zone is greater than 0.1, the occurrence of discharge trace holes in the second annular zone can be suppressed by making the integral value of L(r) in the first annular zone 0 to 0.1, the number of islands in the second annular zone is 20 to 50, and the common logarithm value of the volume resistivity of the second annular zone as a whole is 10.0 LogΩ·cm to 12.5 LogΩ·cm. The reason for this is not yet clear, but it is speculated as follows.

[0073] In a transfer device using an endless belt as a secondary transfer member, when an endless belt having a conductive layer containing an ion conductive organic polymer material and an electron conductive conductivity imparting agent is used as the endless belt, resistance may increase due to repeated application of high voltage with continuous use. The resistance increase is believed to be caused by the partial localization of ions in the conductive layer and the oxidative degradation of the ion conductive organic polymer material.

[0074] Furthermore, as a method for suppressing the above-mentioned resistance increase, for example, a method can be cited in which the number of island portions composed of agglomerates of the above-mentioned electronically conductive conductivity-imparting agent and having a particle size of not less than 100 nm and not more than 3 μm is not less than 20 and not more than 50 in a 10 μm×10 μm square, and the common logarithm value of the volume resistivity of the entire annular zone is not less than 10.0 LogΩ·cm and not more than 12.5 LogΩ·cm.

[0075] However, although the annular belt having the number of island portions and the common logarithm value of the volume resistivity within the above range can suppress the increase in resistance, it is not suitable for a belt having a basis weight of more than 300 g / m 2 In the case of continuous feeding of thick paper, discharge trace holes may be generated on the surface of the endless belt as the secondary transfer component due to abnormal discharge at the end of the paper. In recent years, in order to achieve high speed and high image quality of image forming devices, high voltage (for example, 2.0 kV or more) is sometimes applied to the secondary transfer area. Therefore, it is believed that abnormal discharge is easily caused in the discharge gap at the end of the thick paper. In addition, in a low temperature and low humidity environment, the resistance of the above-mentioned endless belt increases due to the temperature and humidity dependence of the resistance. Therefore, due to the increase in the voltage applied to the secondary transfer area and the continuous feeding of thick paper, it is easy to significantly cause the generation of discharge trace holes. In addition, when further image formation is performed after the discharge trace holes are generated on the outer peripheral surface of the endless belt as the secondary transfer component, the discharge trace holes affect the secondary transfer step, and a white image caused by the discharge trace holes may be formed.

[0076] In contrast, in the present embodiment, the integral value of L(r) in the first endless belt is greater than or equal to 0 and less than or equal to 0.1. That is, the conductive carbon particles are finely dispersed in the outer peripheral surface of the first endless belt. Therefore, it can be inferred that even if a high voltage is applied to the discharge gap at the end of the thick paper, small discharges will occur at each of the conductive points finely dispersed on the outer peripheral surface of the first endless belt, and the current will be dispersed, thereby suppressing abnormal discharge, and it is not easy to generate discharge trace holes caused by abnormal discharge.

[0077] It should be noted that the conductivity in this specification refers to a volume resistivity of less than 1×10 13 Ωcm.

[0078] Next, the first endless belt used as the intermediate transfer member and the second endless belt used as the secondary transfer member will be described respectively.

[0079] <First Endless Belt of the Present Invention>

[0080] The first endless zone contains resin and conductive carbon particles, and the integrated value of L(r) is greater than or equal to 0 and less than or equal to 0.1.

[0081] The first endless belt may be a single-layer body or a laminated body.

[0082] When the first endless belt is a single-layer body, the single-layer body is a layer including a resin and conductive carbon particles, and the integrated value of L(r) is 0 or more and 0.1 or less.

[0083] When the first endless belt is a laminate, the laminate includes, for example, a base layer and a surface layer provided on the base layer. The surface layer is the outermost layer of the first endless belt. The laminate may include another layer between the base layer and the surface layer.

[0084] When the first endless belt is a laminate having a substrate layer and a surface layer, the surface layer is a layer comprising a resin and conductive carbon particles, and the integral value of L(r) is greater than or equal to 0 and less than 0.1. The substrate layer is not particularly limited, and examples thereof include a layer comprising a substrate layer resin and conductive carbon particles for a substrate layer.

[0085] Hereinafter, the layer of the first endless belt as a single layer is referred to as a "single layer". In addition, the surface layer containing the resin and the conductive carbon particles in the first endless belt as a laminate is referred to as the "first layer", and the substrate layer containing the substrate layer resin and the substrate layer conductive carbon particles is referred to as the "second layer". In addition, the resin and the conductive carbon particles contained in the single layer or the first layer are also referred to as the "first resin" and the "first conductive carbon particles", respectively, and the substrate layer resin and the conductive carbon particles contained in the second layer are also referred to as the "second resin" and the "second conductive carbon particles", respectively.

[0086] (resin)

[0087] As the first resin contained in the single layer or the first layer, for example, polyimide resin (PI resin), polyamide-imide resin (PAI resin), aromatic polyetherketone resin (for example, aromatic polyetheretherketone resin, etc.), polyphenylene sulfide resin (PPS resin), polyetherimide resin (PEI resin), polyester resin, polyamide resin, polycarbonate resin, etc. can be cited. From the aspects of mechanical strength and dispersibility of the first conductive carbon particles, the first resin preferably includes at least one selected from the group consisting of polyimide resin, polyamide-imide resin, aromatic polyetherketone resin, polyetherimide resin and polyphenylene sulfide resin, and more preferably includes at least one selected from the group consisting of polyimide resin and polyamide-imide resin. Among them, from the aspect of mechanical strength, polyimide resin is more preferred. The first resin can be composed of one resin or a mixture of two or more resins.

[0088] Specific examples and preferred examples of the second resin contained in the second layer are also the same as those of the first resin. The second resin may be composed of one type of resin or a mixture of two or more types of resins.

[0089] It should be noted that when the first endless belt has the first layer and the second layer, the first resin and the second resin may be the same resin or different resins, and are preferably the same resin (for example, the first resin and the second resin are both polyimide resins).

[0090] -Polyimide resin-

[0091] As a polyimide resin, the imidation product of the polyamic acid (precursor of a polyimide resin) which is a polymer of a tetracarboxylic dianhydride and a diamine compound is mentioned, for example.

[0092] Examples of the polyimide resin include resins having a structural unit represented by the following general formula (I).

[0093] [Chemistry 1]

[0094]

[0095] In the general formula (I), R 1 Represents a 4-valent organic group, R 2 It represents a divalent organic group.

[0096] As R 1 The tetravalent organic group represented by the present invention includes an aromatic group, an aliphatic group, a cyclic aliphatic group, a group formed by combining an aromatic group and an aliphatic group, or a group formed by substitution thereof. Specifically, the tetravalent organic group includes, for example, a residue of tetracarboxylic dianhydride described below.

[0097] As R2 The divalent organic group represented by the compound may be an aromatic group, an aliphatic group, a cycloaliphatic group, a group formed by combining an aromatic group and an aliphatic group, or a group formed by substitution thereof. Specifically, the divalent organic group may be a residue of a diamine compound described below.

[0098] Specific examples of tetracarboxylic dianhydrides used as a raw material for the polyimide resin include pyromellitic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,2'-bis(3,4-dicarboxyphenyl)sulfone dianhydride, perylene-3,4,9,10-tetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, and ethylenetetracarboxylic dianhydride.

[0099] Specific examples of the diamine compound used as a raw material of the polyimide resin include 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, 3,3'-dichlorobenzidine, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 1,5-diaminonaphthalene, m-phenylenediamine, p-phenylenediamine, 3,3'-dimethyl-4,4'-biphenylenediamine, benzidine, 3,3'-dimethylbenzidine, 3,3'-Dimethoxybenzidine, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl propane, 2,4-bis(β-amino tert-butyl) toluene, bis(p-β-amino-tert-butylphenyl) ether, bis(p-β-methyl-δ-aminophenyl) benzene, bis-p-(1,1-dimethyl-5-amino-pentyl) benzene, 1-isopropyl-2,4-m-phenylenediamine, m-phenylenediamine, p-phenylenediamine, di(p-aminocyclohexyl)methane, 1,6-hexanediamine, heptamethylene diamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, diaminopropyltetramethylene, 3-methylheptamethylenediamine, 4,4-dimethylheptamethylenediamine, 2,11-diaminododecane, 1,2-bis-3-aminopropoxyethane, 2,2-dimethylpropylenediamine, 3-methoxy-1,6-hexanediamine, 2,5-dimethylheptamethylenediamine, 3-methylheptamethylenediamine, 5-methyl-1,9-nonanediamine, 2,17-diamino 2,17-diaminoeicosane, 1,4-cyclohexanediamine, 1,10-diamino-1,10-dimethyldecane, 12-diaminooctadecane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, piperazine, H2N(CH2)3O(CH2)2O(CH2)NH2, H2N(CH2)3S(CH2)3NH2, H2N(CH2)3N(CH3)2(CH2)3NH2, etc.

[0100] -Polyamide-imide resin-

[0101] Examples of the polyamide-imide resin include resins having an imide bond and an amide bond in a repeating unit.

[0102] More specifically, examples of the polyamide-imide resin include polymers of a trivalent carboxylic acid compound (also referred to as tricarboxylic acid) having an acid anhydride group and a diisocyanate compound or a diamine compound.

[0103] As the tricarboxylic acid, trimellitic anhydride and its derivatives are preferred. In addition to the tricarboxylic acid, tetracarboxylic dianhydride, aliphatic dicarboxylic acid, aromatic dicarboxylic acid, etc. may be used in combination.

[0104] Examples of the diisocyanate compound include 3,3'-dimethylbiphenyl-4,4'-diisocyanate, 2,2'-dimethylbiphenyl-4,4'-diisocyanate, biphenyl-4,4'-diisocyanate, biphenyl-3,3'-diisocyanate, biphenyl-3,4'-diisocyanate, 3,3'-diethylbiphenyl-4,4'-diisocyanate, 2,2'-diethylbiphenyl-4,4'-diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, 2,2'-dimethoxybiphenyl-4,4'-diisocyanate, naphthalene-1,5-diisocyanate, and naphthalene-2,6-diisocyanate.

[0105] Examples of the diamine compound include compounds having the same structure as the above-mentioned isocyanate and having an amino group instead of an isocyanate group.

[0106] -Aromatic polyetherketone resin-

[0107] Examples of the aromatic polyetherketone resin include resins in which aromatic rings such as a benzene ring are bonded to form a linear chain via an ether bond and a ketone bond.

[0108] As the aromatic polyetherketone resin, for example, there can be mentioned: polyetherketone (PEK) in which ether bonds and ketone bonds are alternately arranged; polyetheretherketone (PEEK) in which ether bonds, ether bonds and ketone bonds are arranged in this order; polyetherketoneketone (PEKK) in which ether bonds, ketone bonds and ketone bonds are arranged in this order; polyetheretherketoneketone (PEEKK) in which ether bonds, ether bonds, ketone bonds and ketone bonds are arranged in this order; polyetheretherketoneketone (PEEKK) in which ether bonds, ether bonds, ketone bonds and ketone bonds are arranged in this order; polyetherketone ester containing ester bonds, etc.

[0109] From the perspective of adjusting mechanical strength and volume resistivity, the content of the first resin relative to the entire monolayer is preferably 60 mass % to 95 mass %, more preferably 70 mass % to 95 mass %, and further preferably 75 mass % to 90 mass %.

[0110] From the perspective of adjusting mechanical strength and volume resistivity, the content of the first resin relative to the entire first layer is preferably 60 mass % to 95 mass %, more preferably 70 mass % to 95 mass %, and further preferably 75 mass % to 90 mass %.

[0111] From the perspective of adjusting mechanical strength and volume resistivity, the content of the second resin relative to the entire second layer is preferably 60 mass % to 95 mass %, more preferably 70 mass % to 95 mass %, and further preferably 75 mass % to 90 mass %.

[0112] (Conductive carbon particles)

[0113] Examples of the first conductive carbon particles contained in the single layer or the first layer include carbon black.

[0114] Examples of carbon black include Ketjen black, oil furnace black, channel black (ie, gas black), and acetylene black. Carbon black having a surface treated (hereinafter also referred to as "surface treated carbon black") may be used.

[0115] Surface treated carbon black is obtained by imparting, for example, carboxyl groups, quinone groups, lactone groups, hydroxyl groups, etc. to its surface. Examples of surface treatment methods include: air oxidation in which the carbon black is exposed to air in a high temperature atmosphere for reaction; a method in which the carbon black is reacted with nitrogen oxides or ozone at room temperature (e.g., 22° C.); a method in which the carbon black is oxidized with air in a high temperature atmosphere and then oxidized with ozone at a low temperature; and the like.

[0116] From the viewpoint of adjusting the L(r) integrated value to the above range, the first conductive carbon particles are preferably channel black among these, and more preferably surface-treated channel black.

[0117] The first conductive carbon particles may be composed of one type of conductive carbon particles or may be a mixture of two or more types of conductive carbon particles.

[0118] Specific examples of the second conductive carbon particles contained in the second layer may also include the same specific examples as the first conductive carbon particles.

[0119] From the viewpoint of controlling the conductivity, the second conductive carbon particles are preferably channel black and furnace black among these, and more preferably carbon black which has not been surface treated.

[0120] The second conductive carbon particles may be composed of one type of conductive carbon particles or may be a mixture of two or more types of conductive carbon particles.

[0121] As the number average primary particle size of the first conductive carbon particles, for example, the range of 20 nm or less can be cited. From the perspective of adjusting the L(r) integral value to the above range, it is preferably in the range of 18 nm or less, more preferably in the range of 15 nm or less, and further preferably in the range of 13 nm or less. In addition, as the number average primary particle size of the first conductive carbon particles, for example, the range of 2 nm or more can be cited. From the perspective of adjusting the L(r) integral value to the above range, it is preferably in the range of 5 nm or more, and more preferably in the range of 10 nm or more.

[0122] The number average primary particle size of the second conductive carbon particles can be, for example, in the range of 2 nm to 40 nm. From the perspectives of dispersibility, mechanical strength, volume resistivity, etc., it is preferably in the range of 20 nm to 40 nm, more preferably in the range of 20 nm to 35 nm, and further preferably in the range of 20 nm to 28 nm.

[0123] When the first endless belt has a first layer and a second layer, the number average primary particle size of the first conductive carbon particles is preferably smaller than the number average primary particle size of the second conductive carbon particles. The number average primary particle size of the first conductive carbon particles is preferably 0.5 times or more and less than 1.0 times the number average primary particle size of the second conductive carbon particles, more preferably 0.5 times or more and 0.8 times or less, and further preferably 0.5 times or more and 0.7 times or less.

[0124] In addition, the number average primary particle size of the first conductive carbon particles is preferably 0.1 times to 1.0 times the number average primary particle size of the electronic conductive conductivity imparting agent contained in the second annular band described later, more preferably 0.1 times to 0.8 times, and further preferably 0.2 times to 0.7 times.

[0125] The number average primary particle size of the conductive carbon particles is measured by the following method.

[0126] First, a 100 nm thick sample was taken from each layer of the obtained tape using a microtome, and the sample was observed using a TEM (transmission electron microscope). After that, the diameter of a circle equal to the projected area of ​​each of 50 conductive carbon particles (i.e., the equivalent circle diameter) was taken as the particle size, and the average value thereof was taken as the number average primary particle size.

[0127] The pH of the first conductive carbon particles may be, for example, in the range of 1.0 to 5.5. From the viewpoint of adjusting the L(r) integrated value to the above range, the pH is preferably in the range of 1.0 to 3.0.

[0128] The pH of the second conductive carbon particles may be, for example, in the range of 1.0 to 5.5. From the viewpoint of adjusting the L(r) integrated value to the above range, the pH is preferably in the range of 1.0 to 4.0.

[0129] When the first endless belt has a first layer and a second layer, the pH of the first conductive carbon particles is preferably lower than the pH of the second conductive carbon particles.

[0130] From the perspective of reducing the L(r) integral value and adjusting the dispersibility, mechanical strength and volume resistivity, the content of the first conductive carbon particles relative to the entire monolayer is preferably at least 10 mass % and at most 50 mass %, more preferably at least 13 mass % and at most 30 mass %, and further preferably at least 15 mass % and at most 25 mass %.

[0131] From the perspective of reducing the L(r) integral value and adjusting the dispersibility, mechanical strength and volume resistivity, the content of the first conductive carbon particles relative to the first layer as a whole is preferably at least 10 mass % and at most 50 mass %, more preferably at least 13 mass % and at most 30 mass %, and further preferably at least 15 mass % and at most 25 mass %.

[0132] From the perspective of adjusting dispersibility, mechanical strength and volume resistivity, the content of the second conductive carbon particles relative to the entire second layer is preferably at least 5 mass % and at most 40 mass %, more preferably at least 10 mass % and at most 30 mass %, and further preferably at least 20 mass % and at most 30 mass %.

[0133] (Other ingredients)

[0134] The single layer, the first layer, and the second layer may each contain other components in addition to the resin and the conductive carbon particles.

[0135] Examples of other components include conductive agents other than conductive carbon particles, fillers for improving the strength of the tape, antioxidants for preventing thermal degradation of the tape, surfactants for improving fluidity, and heat-resistant antioxidants.

[0136] When other components are contained in the above-mentioned layer, the content of the other components is preferably greater than 0 mass % and less than 10 mass %, more preferably greater than 0 mass % and less than 5 mass %, and further preferably greater than 0 mass % and less than 1 mass % relative to the total mass of the target layer.

[0137] (Characteristics of the first annular zone)

[0138] -L(r) integral value of the first annular zone-

[0139] The L(r) integral value of the first annular zone is 0 to 0.1, and is preferably 0 to 0.08, and more preferably 0 to 0.06, from the viewpoint of further suppressing the generation of discharge trace holes in the second annular zone.

[0140] There is no particular limitation on the method for making the L(r) integral value fall within the above range, and examples include a method of using particles having a small number-average primary particle size as the first conductive carbon particles, a method of selecting the type of first conductive carbon particles to be used, a method of adjusting the conditions (such as drying conditions, etc.) during the manufacturing process of the first endless belt, and the like.

[0141] -Thickness of the first annular zone-

[0142] From the viewpoint of the mechanical strength of the tape, the thickness of a single layer is preferably 60 μm to 120 μm, and more preferably 80 μm to 120 μm.

[0143] From the viewpoint of manufacturing suitability and suppression of discharge, the thickness of the first layer is preferably 1 μm to 40 μm, and more preferably 3 μm to 20 μm.

[0144] From the viewpoint of the mechanical strength of the belt, the thickness of the second layer is preferably 50 μm to 100 μm, and more preferably 60 μm to 80 μm.

[0145] When the first endless belt has the first layer and the second layer, the ratio of the first layer to the total thickness is preferably 3% to 50%, more preferably 5% to 30%, from the viewpoint of suppressing the generation of discharge trace holes.

[0146] In addition, the film thickness of each layer was measured as follows.

[0147] Specifically, the cross section of the first endless zone in the thickness direction is observed using an optical microscope or a scanning electron microscope, the thickness of the layer to be measured is measured at 10 locations, and the average value is taken as the thickness.

[0148] - Volume resistivity of the first annular zone -

[0149] From the perspective of suppressing the formation of discharge trace holes, the common logarithm of the volume resistivity when a voltage of 100 V is applied to the first annular belt for 5 seconds is preferably above 9.0 (LogΩ·cm) and below 13.5 (LogΩ·cm), more preferably above 9.5 (LogΩ·cm) and below 13.2 (LogΩ·cm), and particularly preferably above 10.0 (LogΩ·cm) and below 12.5 (LogΩ·cm).

[0150] The volume resistivity of the first endless belt when a voltage of 100 V was applied for 5 seconds was measured by the following method.

[0151] A micro ammeter (R8430A manufactured by Advantest) was used as a resistance measuring machine, and a UR probe (manufactured by Mitsubishi Chemical Analytical Science Co., Ltd.) was used as a probe. The volume resistivity (logΩ·cm) was measured at 6 points at equal intervals along the circumference of the first annular belt, and 3 points were taken at the central part and both ends in the width direction, a total of 18 points, under the conditions of voltage 100V, application time 5 seconds, and pressure 1kgf, and the average value was calculated. In addition, the measurement was performed under an environment of temperature 22°C and humidity 55%RH.

[0152] -Surface resistivity of the first annular zone-

[0153] From the perspective of suppressing the formation of discharge trace holes, the common logarithm of the surface resistivity when a voltage of 100 V is applied to the outer surface of the first annular belt for 3 seconds is preferably at least 10.0 (LogΩ / sq.) and at most 15.0 (LogΩ / sq.), more preferably at least 10.5 (LogΩ / sq.) and at most 14.0 (LogΩ / sq.), and particularly preferably at least 11.0 (LogΩ / sq.) and at most 13.5 (LogΩ / sq.).

[0154] The unit of the surface resistivity, LogΩ / sq., is a resin in which the surface resistivity is expressed as a logarithm of the resistance value per unit area, and is also expressed as Log(Ω / sq.), LogΩ / sq., LogΩ / □, and the like.

[0155] The surface resistivity when a voltage of 100 V was applied to the outer peripheral surface of the first endless belt for 3 seconds was measured by the following method.

[0156] A micro ammeter (R8430A manufactured by Advantest) was used as a resistance measuring machine, and a UR probe (manufactured by Mitsubishi Chemical Analytical Science Co., Ltd.) was used as a probe. The surface resistivity (logΩ / sq.) of the outer peripheral surface of the first endless belt was measured at 6 points at equal intervals along the circumferential direction, and 3 points were taken at the central part and both ends in the width direction, a total of 18 points, under the conditions of voltage 100V, application time 3 seconds, and pressure 1kgf, and the average value was calculated. In addition, the measurement was performed under an environment of temperature 22°C and humidity 55%RH.

[0157] (Method for manufacturing the first endless belt)

[0158] The method for producing the first endless belt is not particularly limited.

[0159] In one example of a method for manufacturing a first endless belt, the following steps are performed: a first coating liquid preparation step of preparing a first coating liquid containing a first resin or a precursor thereof, first conductive carbon particles, and a first solvent; a first coating film formation step of coating the first coating liquid on the periphery of a material to be coated to form a first coating film; and a first drying step of drying the first coating film while raising the temperature of the material to be coated. In addition to the first coating liquid preparation step, the first coating film formation step, and the first drying step, other steps may also be performed in the method for manufacturing the first endless belt. As other steps, for example, when a precursor of the first resin is used, a first firing step of firing the first coating film dried in the first drying step may be cited.

[0160] When manufacturing the first endless belt as a single layer, a single layer including the first resin and the first conductive carbon particles is formed on the outer peripheral surface of the coated material through the first coating liquid preparation step, the first coating film formation step, and the first drying step. It should be noted that the single layer can be formed by, for example, preparing pellets including the first resin and the first conductive carbon particles and melt-extruding the pellets.

[0161] In the case of manufacturing the first endless belt as a laminate, for example, by undergoing the above-mentioned first coating liquid preparation step, the first coating film formation step and the first drying step, the first layer containing the first resin and the first conductive carbon particles is formed on the outer peripheral surface of the second layer formed on the coated material.

[0162] In the case of manufacturing the first endless belt as a laminate, the second layer is formed on the outer peripheral surface of the coated material by, for example, undergoing the following steps: a second coating liquid preparation step of preparing a second coating liquid containing a second resin or a precursor thereof, second conductive carbon particles, and a second solvent; a second coating film formation step of coating the second coating liquid on the outer periphery of the coated material to form a second coating film; and a second drying step of drying the second coating film. It should be noted that the second layer can also be formed by, for example, preparing pellets containing the second resin and the second conductive carbon particles and melt-extruding the pellets.

[0163] -Coating liquid preparation steps-

[0164] In the first coating liquid preparation step, a first coating liquid containing a first resin or a precursor thereof, first conductive carbon particles, and a first solvent is prepared. For example, when the first resin is a polyimide resin and the first conductive carbon particles are carbon black, as the first coating liquid, for example, a solution in which carbon black is dispersed and polyamic acid, which is a precursor of the polyimide resin, is dissolved in the first solvent is prepared. In addition, for example, when the first resin is a polyamide-imide resin and the first conductive carbon particles are carbon black, as the first coating liquid, for example, a solution in which carbon black is dispersed and polyamide-imide resin is dissolved in the first solvent is prepared.

[0165] As a method for preparing the first coating liquid, it is preferred to perform a dispersion treatment using a pulverizer such as a ball mill or a jet mill from the perspective of pulverizing agglomerates of the first conductive carbon particles and improving the dispersibility of the first conductive carbon particles.

[0166] The first solvent is not particularly limited and may be appropriately determined according to the type of resin used as the first resin, etc. For example, when the first resin is a polyimide resin or a polyamide-imide resin, it is preferable to use a polar solvent described below as the first solvent.

[0167] Examples of the polar solvent include N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide (DEAc), dimethyl sulfoxide (DMSO), hexamethylenephosphoramide (HMPA), N-methylcaprolactam, N-acetyl-2-pyrrolidone, and 1,3-dimethyl-2-imidazolidinone (N,N-dimethylimidazolidinone, DMI). These solvents may be used alone or in combination of two or more.

[0168] It should be noted that, in the case of undergoing the second coating liquid preparation step, a second coating liquid containing a second resin, second conductive carbon particles and a second solvent is prepared in the second coating liquid preparation step. The second resin and the second conductive carbon particles are as described above, and the preparation method of the second coating liquid and the second solvent are respectively the same as the preparation method of the first coating liquid and the first solvent.

[0169] -Coating film forming step-

[0170] In the first coating film forming step, the first coating liquid is applied onto the outer periphery of the material to be coated to form a first coating film.

[0171] As the material to be coated, for example, a cylindrical or columnar mold can be cited. The material to be coated can be a material obtained by treating the outer peripheral surface of the above-mentioned mold with a release agent. In the case of manufacturing the first endless belt as a single-layer body, in the first coating film forming step, for example, the first coating liquid is directly coated on the outer peripheral surface of the above-mentioned coated material or the coated material treated with a release agent. In the case of manufacturing the first endless belt as a laminate, in the first coating film forming step, for example, the first coating liquid is coated on the outer peripheral surface of the coated material on which the second layer or the second coating film is formed.

[0172] Examples of the coating method of the first coating liquid include known methods such as spray coating, spiral coating (flow coating), blade coating, wire rod coating, dip coating, bead coating, air knife coating, and curtain coating.

[0173] In the case of the second coating film forming step, the second coating liquid is applied to the outer periphery of the material to be coated to form the second coating film. The coating method of the second coating liquid is also the same as the coating method of the first coating liquid.

[0174] - Drying Step -

[0175] In the first drying step, the first coating film formed in the first coating film forming step is dried. The first solvent contained in the first coating film is removed by the first drying step to obtain a single layer or a first layer.

[0176] Examples of a method for drying the first coating film include a method of supplying hot air to the first coating film and a method of heating the coated material.

[0177] The hot air velocity on the first coating film surface is, for example, in the range of 0.1 m / s to 50.0 m / s, preferably in the range of 1.0 m / s to 40.0 m / s, and more preferably in the range of 1.0 m / s to 20.0 m / s.

[0178] Here, the hot air velocity on the surface of the first coating film is measured as follows: Specifically, it is measured using an anemometer (Anemomaster Model 6036, manufactured by KANOMAX Corporation).

[0179] The hot air temperature on the surface of the first coating film is, for example, in the range of 100°C to 280°C, preferably in the range of 100°C to 250°C, and more preferably in the range of 110°C to 235°C.

[0180] The hot air temperature on the surface of the first coating film is measured by connecting a thermometer (for example, K thermocouple manufactured by Graphtec, model: JBS-7115-5M-K) to a data logger manufactured by Graphtec (model: GL240).

[0181] The method of supplying hot air to the surface of the first coating film is not particularly limited, and examples thereof include a method of blowing hot air from a drying furnace toward the surface of the first coating film from a slit nozzle, a method of directly supplying hot air from a drying furnace to the first coating film, etc. Among them, the method of using a slit nozzle is preferred because it is easy to control the hot air velocity on the surface of the first coating film.

[0182] It should be noted that, in the case of undergoing the second drying step, the second coating film formed by the second coating film forming step is dried in the second drying step. The method of drying the second coating film is the same as the method of drying the first coating film. The second drying step may be completed before the first coating film forming step is performed, or the first coating film forming step may be performed before the second drying step is completed, so that the first drying step also serves as a part of the second drying step.

[0183] -Firing steps-

[0184] As described above, the method for manufacturing the first endless belt may include a first firing step. In the first firing step, the first coating film dried in the first drying step is fired by heating. For example, when the first resin is a polyimide resin, the polyamic acid contained in the first coating film is imidized by the first firing step to obtain a polyimide.

[0185] The heating temperature in the first firing step is, for example, in the range of 150° C. to 450° C., preferably in the range of 200° C. to 430° C. The heating time in the first firing step is, for example, in the range of 20 minutes to 180 minutes, preferably in the range of 60 minutes to 150 minutes.

[0186] It should be noted that, when manufacturing the first endless belt as a laminate, when the second layer is formed through the second coating liquid preparation step, the second coating film formation step, and the second drying step, a second firing step of firing the second coating film dried in the second drying step may be performed. The second firing step may also serve as the first firing step.

[0187] <Second Endless Belt of the Present Invention>

[0188] The second annular belt has a conductive layer, which is arranged on the outer peripheral surface side of the intermediate transfer body, and has a sea portion containing an organic polymer material with ion conductivity and specific island portions composed of agglomerates of a conductivity-imparting agent with electronic conductivity and with a particle size of not less than 100 nm and not more than 3 μm. The number of specific island portions in a 10 μm×10 μm square of the conductive layer is not less than 20 and not more than 50, and the common logarithm value of the overall volume resistivity is not less than 10.0 LogΩ·cm and not more than 12.5 LogΩ·cm.

[0189] The second endless belt is not particularly limited as long as it is an endless belt shape.

[0190] The second endless belt includes, for example, a base layer and a surface layer provided on the outer peripheral surface of the base layer.

[0191] (Base material layer)

[0192] The substrate layer is a conductive layer comprising an ion-conductive organic polymer material and an electronically conductive conductivity imparting agent (hereinafter sometimes referred to as "electronically conductive material"), and is composed of other known additives as needed. The substrate layer has a sea portion comprising an ion-conductive organic polymer material and a specific island portion where the electronically conductive material is agglomerated and has a particle size of 100 nm or more and 3 μm or less, and the number of the above-mentioned specific island portions in a 10 μm×10 μm square (i.e., the number of island portions) is 20 or more and 50 or less.

[0193] -Ion-conductive organic polymer materials-

[0194] The ion conductive organic polymer material constitutes the sea portion in the substrate layer. As the ion conductive organic polymer material contained in the substrate layer, a resin material or a rubber material having conductivity can be cited. From the aspect of elasticity, the ion conductive organic polymer material contained in the substrate layer is preferably a rubber material.

[0195] Examples of the rubber material as the ion-conductive organic polymer material include a rubber material containing polar rubber.

[0196] Examples of polar rubbers include epichlorohydrin rubber (ECO), chloroprene rubber (CR), urethane rubber (U), fluororubber (FKM), epichlorohydrin-ethylene oxide copolymer rubber, epichlorohydrin-ethylene oxide-allyl glycidyl ether copolymer rubber, acrylonitrile-butadiene copolymer rubber (NBR), etc. The rubber material may contain only one type of these polar rubbers or two or more types thereof.

[0197] The rubber material preferably includes at least one selected from the group consisting of epichlorohydrin rubber, chloroprene rubber, and acrylonitrile-butadiene copolymer rubber, and more preferably includes epichlorohydrin rubber.

[0198] The rubber material as the ion conductive organic polymer material may contain other rubbers in addition to the polar rubber described above. That is, the rubber material as the ion conductive organic polymer material may be a mixed rubber of the polar rubber described above and the other rubber described below.

[0199] Examples of other rubbers include isoprene rubber (IR), butyl rubber (IIR), silicone rubber (Q), styrene-butadiene rubber (SBR), butadiene rubber (BR), ethylene propylene rubber (EPM), ethylene-propylene-diene terpolymer rubber (EPDM), natural rubber (NR), and rubbers obtained by mixing these.

[0200] When the rubber material contains other rubber in addition to the polar rubber, the other rubber preferably contains ethylene-propylene-diene terpolymer rubber.

[0201] The content of the rubber material in the base material layer is preferably 50% by mass to 90% by mass, more preferably 70% by mass to 85% by mass, particularly preferably 75% by mass to 80% by mass.

[0202] In addition, from the viewpoint of controlling resistance, the ion conductive organic polymer material is preferably a rubber material mixed with EPDM, CR, ECO and NBR as rubber components. These rubber components are preferably contained in the following mass ratios relative to 100 mass % of the rubber material, for example.

[0203] EPDM: 20% by mass or more and 45% by mass or less (more preferably 35% by mass or more and 40% by mass or less)

[0204] CR: 20 mass % or more and 40 mass % or less (more preferably 30 mass % or more and 35 mass % or less)

[0205] ·ECO: 0 mass % to 20 mass % (more preferably 10 mass % to 15 mass %)

[0206] ·NBR: 0 mass% or more and 15 mass% or less

[0207] -Electronically conductive materials-

[0208] The electron conductive material contained in the substrate layer aggregates in the substrate layer to form islands. For example, among the islands (aggregates) formed by the electron conductive material aggregated in the substrate layer, there are 20 to 50 specific islands with a particle size of 100 nm to 3 μm in a 10 μm×10 μm square.

[0209] From the viewpoint of suppressing the concentration of current in the sea portion due to application of a high voltage and suppressing insulation breakdown between islands, the number of island portions is preferably 25 or more and 40 or less.

[0210] It should be noted that there may be some islands with a particle size of less than 100 nm in the substrate layer, but among the islands produced by the electronically conductive material, the area ratio of specific islands with a size of 100 nm or more and 3 μm or less is preferably 60% or more, more preferably 80% or more, and particularly preferably 100%, that is, there are no islands with a size of less than 100 nm. In addition, islands with a size of more than 3 μm may cause insulation breakdown due to the concentration of electric field in the islands, and therefore, they are preferably absent.

[0211] The electronically conductive material may be at least one selected from the group consisting of carbon black, pyrolytic carbon, graphite, conductive metals or alloys, conductive metal oxides, and surface conductively treated insulating materials.

[0212] Specifically, the electronically conductive material includes, for example, carbon black such as Ketjen black and acetylene black; thermally decomposed carbon; graphite; various conductive metals or alloys such as aluminum, copper, nickel, and stainless steel; various conductive metal oxides such as tin oxide, indium oxide, titanium oxide, tin oxide-antimony oxide solid solution, and tin oxide-indium oxide solid solution; and materials obtained by subjecting the surface of insulating materials to conductive treatment. The electronically conductive material may be used alone or in combination of two or more.

[0213] Among these, carbon black may be used from the aspect of suppressing environmental variation of the resistance of the belt. As carbon black, in particular, from the aspect of stability of resistance over time and electric field dependence of suppressing electric field concentration generated by transfer voltage, oxidation-treated carbon black (for example, carbon black obtained by imparting carboxyl groups, quinone groups, lactone groups, hydroxyl groups, etc. on the surface) at a pH of 5 or less (preferably pH 4.5 or less, more preferably pH 4.0 or less) may be used.

[0214] The electron conductive material has an average primary particle size of 35 nm or less (preferably 24 nm or less, more preferably 16 nm or less). When the electron conductive material has an average primary particle size of this range, the electron conductive material aggregates to form islands with a particle size of 100 nm to 3 μm.

[0215] In particular, when the number average primary particle size of carbon black is 24 nm or less, the conductive paths produced by the carbon black become finer and more uniform, and it is easy to suppress the reduction in resistance due to discharge degradation on the belt surface.

[0216] It should be noted that, based on the above aspect, the smaller the number average primary particle size of carbon black, the better, but if the number average primary particle size is too small, the bulk density will decrease, the handling will become difficult, and the dispersion will show thixotropy due to the increase in specific surface area. Therefore, the number average primary particle size of carbon black can be greater than 10 nm (preferably greater than 12 nm).

[0217] The number average primary particle of carbon black is measured by the following method.

[0218] The substrate layer of the second endless belt was cut with a microtome to obtain a 200 nm thick sample, which was observed with a TEM (transmission electron microscope). Thereafter, the particle sizes of 50 primary particles of carbon black were measured, and the average value was taken as the number average primary particle size.

[0219] The content of the electronically conductive material in the substrate layer depends on the target resistance, and can be 1% by mass or more and 50% by mass or less (preferably 10% by mass or more and 40% by mass or less, and more preferably 20% by mass or more and 30% by mass or less) relative to the entire components constituting the substrate layer. By making the content of the electronically conductive material within this range, it is easy to control the number of island portions to be 20 or more and 50 or less.

[0220] Insulating or semi-conductive particles may be added to the base layer to adjust the volume resistivity of the base layer, for example, silicon dioxide, zinc oxide (zinc white), etc. may be mentioned.

[0221] The following rubber compounding materials may be further used in the base material layer.

[0222] For example, fillers include titanium oxide, magnesium oxide, calcium carbonate, calcium sulfate, clay, talc, etc. In addition, rubber chemicals include vulcanizers, vulcanization accelerators, antioxidants, plasticizers, process oils, etc., and colorants include various pigments, etc.

[0223] In addition, acid acceptors, enhancers, etc. may also be added.

[0224] The thickness of the substrate layer is not particularly limited. For example, from the perspectives of strength, suppression of changes in permanent elongation, prevention of breakage or destruction during belt grinding, surface smoothness, etc., the thickness is preferably from 100 μm to 1000 μm, and more preferably from 300 μm to 600 μm.

[0225] (Surface layer)

[0226] The surface layer is a layer provided on the base material layer as required. The surface layer is composed of, for example, a resin material and a conductive agent, and may contain other known additives as required.

[0227] The base layer made of rubber or the like is prone to wrinkles and discharge products generated during image formation are prone to adhesion. However, by providing a surface layer on the outer peripheral surface of the base layer, the generation of wrinkles and the adhesion of discharge products, toner, etc. can be easily suppressed.

[0228] -Resin-

[0229] Examples of the resin constituting the surface layer include polyurethane resins, polyester resins, and polyacrylic resins.

[0230] -Conductive agent-

[0231] The conductive agent contained in the surface layer is not particularly limited, but may be an electron conductive material, specifically, carbon black, from the viewpoint of suppressing environmental variation in the resistance of the belt.

[0232] As carbon black, in particular, from the perspective of the time stability of resistance and the electric field dependence of suppressing the electric field concentration generated by the transfer voltage, it can be an oxidized carbon black (for example, carbon black obtained by giving carboxyl groups, quinone groups, lactone groups, hydroxyl groups, etc. to the surface) at a pH below 5 (preferably below pH 4.5, more preferably below pH 4.0).

[0233] In addition, the carbon black at pH 5 or less is the same as that explained as the electron conductive material of the substrate layer.

[0234] The content of the conductive agent in the surface layer is selected according to the desired resistance, for example, 1% to 50% by mass, preferably 2% to 40% by mass, and more preferably 4% to 30% by mass, relative to the total components of the constituent layer.

[0235] In addition, the conductive agent in the surface layer may be used alone or in combination of two or more.

[0236] The thickness of the surface layer may be, for example, 2 μm to 30 μm, preferably 5 μm to 15 μm.

[0237] (Characteristics of the second annular zone)

[0238] -Surface resistivity and volume resistivity-

[0239] The common logarithmic value of the volume resistivity in the second endless belt as a whole is 10.0 LogΩ·cm or more and 12.5 LogΩ·cm or less, preferably 10.0 LogΩ·cm or more and 11.6 LogΩ·cm or less. When the common logarithmic value of the volume resistivity in the second endless belt as a whole is 10.0 LogΩ·cm or more, poor transfer of the end of the paper due to the inflow of current into the non-paper feeding area can be suppressed, and when the common logarithmic value is 12.5 LogΩ·cm or less, poor conditions caused by discharge caused by an increase in the transfer voltage can be suppressed.

[0240] The common logarithm value of the surface resistivity of the outer peripheral surface of the second endless zone is preferably 8.5 LogΩ / □ or more and 11.0 LogΩ / □ or less, and more preferably 10.0 LogΩ / □ or more and 11.0 LogΩ / □ or less.

[0241] The surface resistivity is measured as follows: Using a circular electrode (for example, "UR probe" of high resistivity meter IP manufactured by Mitsubishi Petrochemical Corporation), the measurement is performed in accordance with JIS K6911 (1995). The surface resistivity measurement method is described with reference to the drawings. Figure 1 1 and 2 are a schematic plan view (A) and a schematic cross-sectional view (B) showing an example of a circular electrode. Figure 1 The circular electrode shown has a first voltage applying electrode A and a plate-like insulator B. The first voltage applying electrode A has a cylindrical electrode portion C and a cylindrical annular electrode portion D, the inner diameter of the annular electrode portion D being larger than the outer diameter of the cylindrical electrode portion C and surrounding the cylindrical electrode portion C at a certain interval. The tape T is clamped between the cylindrical electrode portion C and the annular electrode portion D in the first voltage applying electrode A and the plate-like insulator B, and the current I (A) flowing when a voltage V (V) is applied between the cylindrical electrode portion C and the annular electrode portion D in the first voltage applying electrode A is measured, and the surface resistivity ρs (Ω / □) of the transfer surface of the tape T is calculated by the following formula. Here, in the following formula, d (mm) represents the outer diameter of the cylindrical electrode portion C, and D (mm) represents the inner diameter of the annular electrode portion D.

[0242] Formula: ρs=π×(D+d) / (Dd)×(V / I)

[0243] It should be noted that the surface resistivity was calculated by using a circular electrode (UR probe of high resistivity meter IP manufactured by Mitsubishi Petrochemical Corporation: outer diameter of cylindrical electrode part C is Φ16 mm, inner diameter of annular electrode part D is Φ30 mm, outer diameter is Φ40 mm), and the current value after applying a voltage of 500 V for 10 seconds in an environment of 22°C / 55%RH was obtained.

[0244] On the other hand, the volume resistivity is measured using a circular electrode (for example, UR probe of high resistivity meter IP manufactured by Mitsubishi Petrochemical Corporation) in accordance with JIS K6911 (1995). Figure 1 The volume resistivity is measured using the same apparatus as the surface resistivity. Figure 1 The circular electrode shown in the figure is provided with a second voltage applying electrode B' instead of the plate-shaped insulator B when measuring the surface resistivity. In addition, the tape T is clamped between the cylindrical electrode portion C and the annular electrode portion D in the first voltage applying electrode A and the second voltage applying electrode B', and the current I (A) flowing when the voltage V (V) is applied between the cylindrical electrode portion C in the first voltage applying electrode A and the second voltage applying electrode B' is measured, and the volume resistivity ρv (Ωcm) of the tape T is calculated by the following formula. Here, in the following formula, t represents the thickness of the tape T.

[0245] Formula: ρv=19.6×(V / I)×t

[0246] It should be noted that the volume resistivity was calculated by using a circular electrode (UR probe of a high resistivity meter IP manufactured by Mitsubishi Petrochemical Corporation: the outer diameter of the cylindrical electrode part C was Φ16 mm, the inner diameter of the annular electrode part D was Φ30 mm, and the outer diameter was Φ40 mm) and the current value after applying a voltage of 500 V for 10 seconds in an environment of 22°C / 55% RH.

[0247] In addition, the 19.6 in the above formula is used to convert the electrode coefficient of resistivity, which is calculated from the outer diameter d (mm) of the cylindrical electrode part, the thickness t (cm) of the sample and πd 2 The thickness of the tape T was measured using an eddy current film thickness meter CTR-1500E manufactured by Sanko Electric.

[0248] The surface resistivity and volume resistivity in the second endless zone are controlled by the type of the ion conductive organic polymer material, the type of the electron conductive material, the amount of the electron conductive material added, and the like.

[0249] (Method for producing conductive member)

[0250] The manufacturing method of the second endless belt is not particularly limited. For example, in the case of manufacturing the above-mentioned endless belt having a substrate layer and a surface layer, the substrate layer may be a structure having a sea portion containing an ion conductive organic polymer material and an island portion composed of aggregates of an electron conductive material. For example, after forming the substrate layer as described below, the surface layer is formed on the outer peripheral surface of the substrate layer, thereby manufacturing the conductive component.

[0251] First, to form the base layer, a rubber composition mixed with a rubber material such as chloroprene rubber or EPDM, an electronically conductive material, a vulcanizing agent, a vulcanization accelerator, etc. is put into a Banbury mixer and kneaded.

[0252] The kneaded product fully kneaded by rollers is further formed into an endless belt shape by a tube crosshead extruder, and the rubber composition formed into an endless belt shape is heated by pressurized steam in a vulcanizer to vulcanize it to form a base rubber. The obtained base material is wrapped around the outside of a metal pipe, and the surface is polished to obtain an endless belt-shaped base material layer.

[0253] It should be noted that the kneading of the rubber composition is not limited to the Banbury mixer, and examples thereof include closed-type kneading machines such as a pressure kneader and open-type kneading machines such as an open roll mill.

[0254] When the base material layer is formed as described above, for example, after preparing a rubber composition obtained by kneading EPDM and CB in advance, other rubber materials, electronically conductive materials, vulcanizing agents, vulcanization accelerators, etc. are mixed and the rubber composition is kneaded. At this time, agglomerates of the electronically conductive material are easily formed, for example, specific islands are easily formed and the number of the islands is set to be 20 or more and 50 or less. It should be noted that the particle size of the agglomerates of the electronically conductive material in the rubber composition can be adjusted by sieving the agglomerates of the electronically conductive material on a sieve as needed.

[0255] The method for forming a surface layer on the outer peripheral surface of the substrate layer is not particularly limited. For example, a surface layer forming coating liquid dispersed with a resin and a conductive agent is applied to the substrate layer by dip coating, spraying, electrostatic coating, roller coating, etc., and then the surface layer is formed by drying.

[0256] [Image forming apparatus]

[0257] The image forming device of this embodiment comprises: an image holder; a charging device for charging the surface of the image holder; an electrostatic latent image forming device for forming an electrostatic latent image on the charged surface of the image holder; a developing device for storing a developer containing a toner and developing the electrostatic latent image formed on the surface of the image holder using the developer to form a toner image; and a transfer device for transferring the toner image to the surface of a recording medium, and the transfer device is used as the transfer device.

[0258] The image forming device of this embodiment includes, for example: a normal monochrome image forming device in which only monochrome toner is stored in a developing device; a color image forming device that repeatedly transfers the toner image held on an image holding body to an intermediate transfer belt in sequence; and a tandem color image forming device in which two or more image holding bodies equipped with developers of different colors are arranged in series on the intermediate transfer belt.

[0259] Figure 2 This is a schematic structural diagram showing an example of the image forming apparatus according to the present embodiment. Figure 2 The image forming apparatus shown is an image forming apparatus in which the first endless belt in the above-mentioned transfer device is applied to the intermediate transfer belt 107 , and the second endless belt is applied to the secondary transfer belt 116 .

[0260] like Figure 2 As shown, the image forming apparatus 100 of the present embodiment is, for example, a so-called tandem type, and charging devices 102a to 102d, exposure devices 114a to 114d, developing devices 103a to 103d, primary transfer devices (primary transfer rollers) 105a to 105d, and image holder cleaning devices 104a to 104d are sequentially arranged around four image holders 101a to 101d formed by electrophotographic photosensitive bodies along their rotation direction. It should be noted that in order to remove the residual potential remaining on the surface of the image holders 101a to 101d after transfer, a static remover may be provided.

[0261] The intermediate transfer belt 107 is supported by the support rollers 106a to 106d, the drive roller 111, and the counter roller 108 while being tensioned, thereby forming a transfer unit 107b. The intermediate transfer belt 107 can move between each image holder 101a to 101d and the primary transfer rollers 105a to 105d in the direction of arrow A while being in contact with the surface of each image holder 101a to 101d by means of the support rollers 106a to 106d, the drive roller 111, and the counter roller 108. The portion where the primary transfer rollers 105a to 105d contact the image holders 101a to 101d across the intermediate transfer belt 107 is the primary transfer portion, and a primary transfer voltage is applied to the contact portion between the image holders 101a to 101d and the primary transfer rollers 105a to 105d.

[0262] As a secondary transfer device, an opposing roller 108 and a secondary transfer roller 109 are arranged opposite to each other with the intermediate transfer belt 107 and the secondary transfer belt 116 interposed therebetween. The secondary transfer belt 116 is supported by the secondary transfer roller 109 and the support roller 106e. A recording medium 115 such as paper is moved in the direction of arrow B to a region sandwiched between the intermediate transfer belt 107 and the secondary transfer roller 109 while in contact with the surface of the intermediate transfer belt 107, and then passes through the fixing device 110. The portion where the secondary transfer roller 109 contacts the opposing roller 108 with the intermediate transfer belt 107 and the secondary transfer belt 116 interposed therebetween is a secondary transfer portion, and a secondary transfer voltage is applied to the contact portion between the secondary transfer roller 109 and the opposing roller 108. Furthermore, intermediate transfer belt cleaning devices 112 and 113 are arranged so as to contact the intermediate transfer belt 107 after transfer.

[0263] In the multi-color image forming apparatus 100 of this structure, the image holder 101a rotates in the direction of arrow C, and its surface is charged by the charging device 102a, and then an electrostatic latent image of the first color is formed by an exposure device 114a such as a laser. The formed electrostatic latent image is developed (imaged) by a developing device 103a storing a toner corresponding to the color using a developer containing a toner to form a toner image. It should be noted that the toners corresponding to the electrostatic latent images of each color (e.g., yellow, magenta, cyan, and black) are stored in the developing devices 103a to 103d, respectively.

[0264] The toner image formed on the image holding body 101a is electrostatically transferred (primary transfer) by the primary transfer roller 105a onto the intermediate transfer belt 107 when passing through the primary transfer section. Then, the toner images of the second color, the third color, and the fourth color are primary transferred by the primary transfer rollers 105b to 105d onto the intermediate transfer belt 107 holding the toner image of the first color so that the toner images of the second color, the third color, and the fourth color are sequentially overlapped, thereby finally obtaining a multi-color toner image.

[0265] The multiple toner images formed on the intermediate transfer belt 107 are electrostatically transferred together onto the recording medium 115 transported by the secondary transfer belt 116 when passing through the secondary transfer section. The recording medium 115 to which the toner images have been transferred is transported to the fixing device 110, and after being fixed by heating and pressurizing, or by heating or pressurizing, it is discharged outside the machine.

[0266] After the primary transfer, the image holders 101a to 101d are cleaned of residual toner by image holder cleaning devices 104a to 104d. On the other hand, after the secondary transfer, the intermediate transfer belt 107 is cleaned of residual toner by intermediate transfer belt cleaning devices 112 and 113 and is placed in the next image forming process.

[0267] (Image holding body)

[0268] As the image holders 101a to 101d, known electrophotographic photoreceptors are widely used. As electrophotographic photoreceptors, inorganic photoreceptors whose photosensitive layers are composed of inorganic materials, organic photoreceptors whose photosensitive layers are composed of organic materials, etc. are used. Among organic photoreceptors, functional separation type organic photoreceptors in which a charge generating layer that generates charges by exposure and a charge transporting layer that transports charges are stacked are suitable; and single-layer organic photoreceptors that have the function of generating charges and the function of transporting charges are suitable. In addition, among inorganic photoreceptors, photoreceptors whose photosensitive layers are composed of amorphous silicon are suitable.

[0269] The shape of the image holding member is not particularly limited, and for example, a known shape such as a cylindrical drum, a sheet, or a plate may be adopted.

[0270] (Charging device)

[0271] There is no particular limitation on the charging devices 102a to 102d, and for example, contact chargers using conductive rollers, brushes, films or rubber blades, scorotron chargers or corotron chargers using corona discharge, and other well-known chargers are widely used. Among them, contact chargers are preferred.

[0272] The charging devices 102a to 102d usually apply direct current to the image holders 101a to 101d, but may also apply alternating current in a superimposed manner.

[0273] (Exposure device)

[0274] There are no particular restrictions on the exposure devices 114a to 114d, and known exposure devices include widely used light sources such as semiconductor lasers, LED (Light Emitting Diode) light, or liquid crystal shutter light, or optical equipment that can expose images determined by these light sources via a prism.

[0275] (Developing device)

[0276] The developing devices 103a to 103d are selected according to the purpose, and examples thereof include known developers that develop a single-component developer or a two-component developer by a contact or non-contact method using a brush or a roller.

[0277] (Primary transfer roller)

[0278] The primary transfer rollers 105a to 105d may be single-layer or multi-layer. For example, in the case of a single-layer structure, they are rollers made of foamed or non-foamed silicone rubber, urethane rubber, EPDM, etc., with an appropriate amount of conductive particles such as carbon black mixed therein.

[0279] (Image holding body cleaning device)

[0280] The image holder cleaning devices 104a to 104d are used to remove residual toner attached to the surfaces of the image holders 101a to 101d after the primary transfer step. In addition to the cleaning blade, brush cleaning or roller cleaning is also used. Among them, the cleaning blade is preferably used. In addition, as the material of the cleaning blade, urethane rubber, chloroprene rubber, silicone rubber, etc. can be cited.

[0281] (Secondary transfer roller)

[0282] The layer structure of the secondary transfer roller 109 is not particularly limited. For example, in the case of a three-layer structure, it is composed of a core layer, an intermediate layer, and a coating layer covering the surface thereof. The core layer is composed of a foamed body such as silicone rubber, urethane rubber, or EPDM in which conductive particles are dispersed, and the intermediate layer is composed of a non-foamed body thereof. Examples of the material of the coating layer include tetrafluoroethylene-hexafluoropropylene copolymers and perfluoroalkoxy resins. The volume resistivity of the secondary transfer roller 109 is preferably 10 7 In addition, a two-layer structure excluding the intermediate layer may be used.

[0283] (Opposing Roller)

[0284] The counter roller 108 forms a counter electrode of the secondary transfer roller 109. The layer structure of the counter roller 108 may be either a single layer or a multilayer. For example, in the case of a single layer structure, it is composed of a roller in which conductive particles such as carbon black are appropriately mixed in silicone rubber, urethane rubber or EPDM. In the case of a two-layer structure, it is composed of a roller in which the outer peripheral surface of an elastic layer composed of the above-mentioned rubber material is coated with a high resistance layer.

[0285] A voltage of usually 1 kV or more and 6 kV or less is applied to the core of the counter roller 108 and the secondary transfer roller 109. Instead of applying a voltage to the core of the counter roller 108, a voltage may be applied to an electrode member with good conductivity in contact with the counter roller 108 and the secondary transfer roller 109. Examples of the electrode member include a metal roller, a conductive rubber roller, a conductive brush, a metal plate, or a conductive resin plate.

[0286] (Fixing device)

[0287] As the fixing device 110 , for example, a well-known fixing device such as a heat roller fixing device, a pressure roller fixing device, or a flash fixing device is widely used.

[0288] (Intermediate transfer belt cleaning device)

[0289] As the intermediate transfer belt cleaning devices 112 and 113, in addition to the cleaning blade, brush cleaning or roller cleaning can also be applied, among which the cleaning blade is preferably used. In addition, as the material of the cleaning blade, urethane rubber, chloroprene rubber or silicone rubber can be cited.

[0290] (Recording Medium)

[0291] Examples of the recording medium 115 include paper, coated paper obtained by coating the surface of paper with a resin or the like, cloth, nonwoven fabric, resin film, and resin sheet.

[0292] The thickness of the recording medium 115 is, for example, in the range of 50 μm to 300 μm. In this embodiment, since the L(r) integral value in the first annular zone is 0 to 0.1, the discharge trace holes in the second annular zone can be suppressed even if the thickness of the recording medium is 300 μm or more.

[0293] The basis weight of the recording medium 115 is, for example, 50 g / m 2 Above 400g / m 2 In this embodiment, since the L(r) integral value in the first endless zone is 0 or more and 0.1 or less, even if the basis weight of the recording medium is greater than 300 g / m 2 , and the discharge trace hole of the second annular band can also be suppressed.

[0294] Although the present embodiment has been described above, it should be understood that the present invention is not limited to the above-described embodiment, and various modifications, changes, and improvements may be made.

[0295] [Example]

[0296] The following is an explanation of examples of the present invention, but the present invention is not limited to the following examples. It should be noted that in the following description, "parts" and "%" are all based on mass unless otherwise specified.

[0297] [Preparation of Intermediate Transfer Body (First Endless Belt)]

[0298] <Preparation of Intermediate Transfer Body A>

[0299] 36 g (20 phr) of oxidized gas black (Orion Engineered Carbons S.A., FW200, number average primary particle size: 13 nm) as the first conductive carbon particles were added to 1000 g of a wholly aromatic polyimide varnish (solid content: 18 wt%, manufactured by Unitika, U-Imide KX, solvent: NMP), and the resulting components were passed through a high pressure collision disperser (manufactured by Genus) at a pressure of 200 MPa. The slurry was dispersed by causing the two divided slurries to collide five times, thereby obtaining a coating liquid A as a first coating liquid.

[0300] The obtained coating liquid A was applied to the surface of the substrate by flow coating so as to obtain a predetermined film thickness. The outer surface of the SUS tube was dried at 150°C for 30 minutes, placed in an oven at 340°C for 1 hour, and then taken out to obtain a SUS tube blank with an annular band 1A formed on the outer surface. The overall film thickness of the annular band 1A (i.e., the film thickness of a single layer) was 80 μm.

[0301] The endless belt 1A coated on the outer surface was removed from the SUS base tube and cut into a width of 360 mm to obtain a belt-shaped intermediate transfer body A. The content of the conductive carbon particles relative to the entire intermediate transfer body A was 16.7% by mass.

[0302] The volume resistivity and the surface resistivity of the outer peripheral surface of the intermediate transfer body A were measured by the above-mentioned method. As a result, the common logarithm value of the volume resistivity was 10.1 (LogΩ·cm).

[0303] <Preparation of Intermediate Transfer Body B>

[0304] As the first conductive carbon particles, 37.8 g (21 phr) of oxidized gas black (Orion Engineered Carbons SA, FW200, number average primary particle size: 13 nm) was used, and the slurry was collided 10 times using a high-pressure collision type disperser (Genus). The endless belt 1B was obtained in the same manner as the endless belt 1A to obtain an intermediate transfer body B as a belt-shaped intermediate transfer body. The overall film thickness of the endless belt 1B (i.e., the film thickness of a single layer) was 80 μm. In addition, the content of the conductive carbon particles relative to the entire intermediate transfer body B was 17.4% by mass.

[0305] The volume resistivity and the surface resistivity of the outer peripheral surface of the intermediate transfer body B were measured by the above-mentioned method. As a result, the common logarithm value of the volume resistivity was 10.0 (LogΩ·cm).

[0306] <Preparation of Intermediate Transfer Body C>

[0307] As the first conductive carbon particles, 50.4 g (28 phr) of oxidized gas black (manufactured by Orion Engineered Carbons SA, SB4, number average primary particle size: 25 nm) was used, and the endless belt 1C was obtained in the same manner as the endless belt 1A, thereby obtaining an intermediate transfer body C as a belt-shaped intermediate transfer body. The overall film thickness (i.e., the film thickness of a single layer) of the endless belt 1C was 80 μm. In addition, the content of the conductive carbon particles relative to the entire intermediate transfer body C was 21.9% by mass.

[0308] The volume resistivity and the surface resistivity of the outer peripheral surface of the intermediate transfer body C were measured by the above-mentioned method. As a result, the common logarithm value of the volume resistivity was 10.0 (LogΩ·cm).

[0309] [Manufacturing of the Secondary Transfer Belt (Second Endless Belt)]

[0310] <Production of Secondary Transfer Belt A1>

[0311] (Production of base rubber layer)

[0312] The following components were mixed in the ratios shown in Table 1 to prepare rubber compositions.

[0313] EPDM: (ethylene propylene diene rubber, EP33 manufactured by JSR Corporation)

[0314] CR: (Chloroprene rubber, TSR-61 manufactured by Tosoh Corporation)

[0315] ECO: (epichlorohydrin rubber, manufactured by Da Cao Co., Ltd. 610)

[0316] NBR: (nitrile rubber, DN211 manufactured by Zeon Co., Ltd.)

[0317] Electronic conductive material: CB (carbon black, Mitsubishi Chemical Corporation #3030B, number average primary particle size: 55 nm)

[0318] Sulfur: (manufactured by Tsurumi Chemical Industries, Ltd.)

[0319] ZnO: (manufactured by Kyodo Chemical Co., Ltd.)

[0320] Vulcanization accelerator: (manufactured by Ouchi Shinko Chemical Industry Co., Ltd., NOCCELER M)

[0321] Stearic acid:

[0322] The above components were mixed in the ratios shown in Table 1, and the obtained rubber composition was put into a Banbury mixer for kneading, and then the rubber composition was kneaded using a twin roll. The obtained kneaded product was formed into an endless belt shape using a tubular crosshead extruder.

[0323] Next, the rubber composition formed into an endless belt shape was subjected to a vulcanization in an autoclave using pressurized steam (temperature 126°C, pressure 1.5 kg / cm 2 ) was heated to vulcanize it and form a base rubber. The obtained base rubber was wrapped around the outside of a metal pipe, and the surface was polished to produce an annular belt-shaped base rubber layer (diameter 40 mm, width 340 mm, thickness 492 μm).

[0324] (Production of surface layer)

[0325] 20 parts by mass of carbon black "FW200" manufactured by Orion Engineered Carbons SA was mixed with 100 parts by mass of silicone-modified urethane acrylic acid (JYL841 manufactured by Nippon Acheson) to prepare a coating liquid for forming a surface layer.

[0326] The coating liquid for forming a surface layer was sprayed onto the surface of the produced base rubber layer, and then heated and dried at 180° C. for 30 minutes to form a surface layer (thickness: 8 μm).

[0327] The secondary transfer belt A1 having a diameter of 40 mm, a width of 340 mm, and a thickness of 500 μm was produced by the above method.

[0328] <Production of Secondary Transfer Belts A2, A3, B1, B2, and C1>

[0329] Secondary transfer belts A2, A3, B1, B2, and C1 were prepared in the same manner as the secondary transfer belt A1 except that the blending and kneading methods of the rubber compositions were changed according to Table 1.

[0330] [Table 1]

[0331]

[0332] [Measurement of annular zone]

[0333] The L(r) integral value in the intermediate transfer body, the number of islands in the secondary transfer belt, the ratio of the area of ​​a specific island in the secondary transfer belt to the area of ​​the entire island, and the common logarithm of the volume resistivity of the secondary transfer belt were measured by the above method. The results are shown in Table 2.

[0334] [Production of Image Forming Device]

[0335] <Production of Image Forming Apparatus>

[0336] The combination of the intermediate transfer body and the secondary transfer belt shown in Table 2 was assembled into a modified image forming apparatus (Versant 2000 manufactured by Fuji Xerox Co., Ltd.) (i.e., a modified apparatus modified so as to be able to carry a secondary transfer belt) to obtain the image forming apparatuses of Examples 1 to 4, Comparative Examples 1 to 4, and Reference Examples 1 to 2.

[0337] [evaluate]

[0338] <Evaluation of transferability>

[0339] In an environment of 10°C and 15% RH, for paper (A3, J paper, basis weight: 82g / m 2 100 sheets of halftone images with an image density of 200% were continuously formed on the paper (paper thickness: 97 μm, manufactured by Fuji Xerox Co., Ltd.). The image quality of the obtained images was evaluated as follows. The evaluation criteria are as follows. The results are shown in Table 2.

[0340] A: No color unevenness occurs on the image

[0341] B: No visually identifiable color unevenness occurs in the image

[0342] C: Slight color unevenness occurs

[0343] D: Color unevenness and color leakage occur partially

[0344] E: The entire image has uneven colors and color leakage

[0345] <Evaluation of Resistance Increase of Secondary Transfer Member>

[0346] In an environment of 10°C and 15% RH, for paper (A3, J paper, basis weight: 82g / m 2 , paper thickness: 97μm, manufactured by Fuji Xerox Co., Ltd.) to continuously form 800,000 sheets of halftone images with an image density of 200%. The change in volume resistance before and after paper feeding (forming 800,000 images) was measured using the above-mentioned resistance measurement method, and the change in resistance due to power supply was calculated and evaluated according to the following evaluation criteria. The results are shown in Table 2.

[0347] A: The resistance difference before and after power on is less than 0.2 [LogΩ·cm]

[0348] B: The resistance difference before and after power on is 0.2 [LogΩ·cm] or more and less than 0.5 [LogΩ·cm]

[0349] C: The resistance difference before and after power on is 0.5 [LogΩ·cm] or more and less than 1.5 [LogΩ·cm]

[0350] D: The resistance difference before and after power on is 1.5 [LogΩ·cm] or more

[0351] <Evaluation of Discharge Trace Holes of Secondary Transfer Member>

[0352] In an environment of 10°C and 15% RH, for thick paper (A3, basis weight: 300 g / m 2 ) 100,000 sheets of halftone images with an image density of 200% were continuously formed. The surface of the secondary transfer member after paper feeding (100,000 sheets of images were formed) was observed to confirm the generation of discharge traces and evaluated according to the following evaluation criteria. The results are shown in Table 2.

[0353] A: No discharge trace hole

[0354] B: Slight discharge marks are produced, but there is no problem with the image quality

[0355] C: Several discharge holes are formed. Color leakage occurs in the image.

[0356] D: A large number of discharge holes are generated. Color leakage occurs in the image.

[0357] [Table 2]

[0358]

[0359] From the results shown in Table 2, it can be seen that the present embodiment can suppress the generation of discharge trace holes in the secondary transfer member compared with Comparative Example 1. It can also be seen that the present embodiment can suppress the increase in resistance compared with Comparative Examples 2 and 4, and can achieve both suppression of the increase in resistance and suppression of the generation of discharge trace holes.

Claims

1. A transfer device comprising: The intermediate transfer body as the first endless belt is a first endless belt comprising a resin and conductive carbon particles, wherein in the spatial distribution of the conductive carbon particles existing in the evaluation area of ​​6.3 μm×4.2 μm on the outer peripheral surface, the integral value of the statistic L(r) represented by the following formula (1) in which the inter-particle distance r is 0.05 μm or more and 0.30 μm or less is 0 or more and 0.1 or less; a primary transfer mechanism for primarily transferring the toner image formed on the surface of the image holding body to the surface of the intermediate transfer body; and A secondary transfer mechanism, the secondary transfer mechanism having a second endless belt arranged on the outer peripheral surface side of the above-mentioned intermediate transfer body, the secondary transfer mechanism secondarily transfers the above-mentioned toner image transferred to the surface of the above-mentioned intermediate transfer body to the surface of the recording medium on the above-mentioned second endless belt, the above-mentioned second endless belt has a conductive layer, the conductive layer has a sea part containing an ion conductive organic polymer material and an island part composed of an aggregate of an electronic conductive conductivity imparting agent and having a particle size of 100nm or more and 3μm or less, the number of the above-mentioned island parts in a 10μm×10μm square of the above-mentioned conductive layer is 20 or more and 50 or less, and the common logarithm value of the volume resistivity of the above-mentioned second endless belt as a whole is 10.0LogΩ·cm or more and 12.5LogΩ·cm or less, In the above formula (1), r represents the above inter-particle distance, and K(r) represents Ripley's K function K(r) represented by the following formula (2): In the above formula (2), 1(|X i -X j |≦r) represents the indicator function, X i and X j Represent the coordinates of point i and point j respectively, |X i -X j | represents coordinate X i With coordinate X j The Euclidean distance, r represents the distance between the above particles, s(|X i -X j |) represents the edge correction coefficient s(x) of the evaluation area represented by the following formula (3), x=|X i -X j |, N represents the total number of particles in the evaluation area, λ represents the number density of particles in the evaluation area, In the above formula (3), L x and L y represents the length of the side in the x-axis direction and the y-axis direction of the evaluation area (μm), x=|X i -X j |, X i and X j Represent the coordinates of point i and point j respectively, |X i -X j | represents coordinate X i With coordinate X j The Euclidean distance of .

2. The transfer device according to claim 1, wherein: The common logarithm value of the volume resistivity of the second annular zone as a whole is not less than 10.0 LogΩ·cm and not more than 11.6 LogΩ·cm.

3. The transfer device according to claim 1 or claim 2, wherein: The above-mentioned organic polymer material is a rubber material.

4. The transfer device according to claim 3, wherein: The rubber material includes at least one selected from the group consisting of epichlorohydrin rubber, chloroprene rubber and acrylonitrile-butadiene copolymer rubber.

5. The transfer device according to claim 3 or claim 4, wherein: The rubber material includes epichlorohydrin rubber, chloroprene rubber, acrylonitrile-butadiene copolymer rubber and ethylene-propylene-diene terpolymer rubber.

6. The transfer device according to any one of claims 1 to 5, wherein: The conductivity-imparting agent is carbon black.

7. The transfer device according to any one of claims 1 to 6, wherein: The resin includes at least one selected from the group consisting of polyimide resin, polyamideimide resin, aromatic polyetheretherketone resin, polyphenylene sulfide resin, and polyetherimide resin.

8. The transfer device according to claim 7, wherein: The above-mentioned resin includes a polyimide resin.

9. The transfer device according to any one of claims 1 to 8, wherein: The number average primary particle size of the conductive carbon particles is not less than 10 nm and not more than 20 nm.

10. The transfer device according to claim 9, wherein: The number average primary particle size of the conductive carbon particles is not less than 10 nm and not more than 15 nm.

11. The transfer device according to any one of claims 1 to 7, wherein: The conductive carbon particles are channel black.

12. The transfer device according to any one of claims 1 to 11, wherein: The number average primary particle size of the conductive carbon particles is 0.1 to 1.0 times the number average primary particle size of the electronically conductive conductivity-imparting agent.

13. An image forming apparatus comprising: Image holding body, A charging device is used to charge the surface of the image holding body. An electrostatic latent image forming device forms an electrostatic latent image on the charged surface of the image holding body. a developing device storing a developer including a toner, and developing the electrostatic latent image formed on the surface of the image holding member using the developer to form a toner image, and The transfer device according to any one of claims 1 to 12 transfers the toner image to a surface of a recording medium.

Citation Information

Patent Citations

  • Intermediate transfer belt

    JP2007011117A

  • Conductive member for image forming apparatus, transfer unit for image forming apparatus, and image forming apparatus

    JP2017181604A

  • Endless belt, method for producing the endless belt, transfer device, and image forming apparatus

    CN112925181A

  • Transfer unit, transfer apparatus, and image forming apparatus

    CN113031419A